2001
DOI: 10.1002/micr.1013
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for ischemic pain and Raynaud's' phenomenon in scleroderma: A description of treatment protocol and evaluation of results

Abstract: Although the literature suggests that palmar sympathectomy (PS) with or without vascular reconstruction may improve ischemic digital pain, fingertip ulceration, and cold intolerance in patients with scleroderma, the question regarding long-term efficacy still remains. This retrospective study of six patients (eight hands) operated on between 1995 and 1997 evaluates both early (6 months) and long-term (average, 2.5 years) outcome after PS in combination with decompression arteriolysis of the radial and ulnar ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 25 publications
1
28
0
2
Order By: Relevance
“…Surgical therapy includes arterial bypass, digital arterial reconstruction, sympathectomy (peripheral and digital) and amputation [12][13][14][15]. Recently botulinum toxin injection and local or intramuscular injection of mesenchymal stem cell have been used in the management of patients with digital ischemia due to secondary RP [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical therapy includes arterial bypass, digital arterial reconstruction, sympathectomy (peripheral and digital) and amputation [12][13][14][15]. Recently botulinum toxin injection and local or intramuscular injection of mesenchymal stem cell have been used in the management of patients with digital ischemia due to secondary RP [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Six of seven patients (and all four patients of this series who had scleroderma) experienced healing of digital ulcers after digital artery sympathectomy, performed as a salvage procedure to prevent amputation [46]. Long-term results (average length of follow-up 2.5 years, range 18 to 40 months) were recently reported in six patients with SSc who had undergone palmar sympathectomy in eight hands, and indications included increasing pain or Raynaud's phenomenon or non-healing digital ulceration [47]. Debridements, amputations, decompression arteriolysis of the radial and ulnar arteries proximal to the wrist, and vascular reconstruction were also performed at the same time, if indicated, reflecting the complexity of the surgical management issues [47].…”
Section: Surgerymentioning
confidence: 95%
“…Long-term results (average length of follow-up 2.5 years, range 18 to 40 months) were recently reported in six patients with SSc who had undergone palmar sympathectomy in eight hands, and indications included increasing pain or Raynaud's phenomenon or non-healing digital ulceration [47]. Debridements, amputations, decompression arteriolysis of the radial and ulnar arteries proximal to the wrist, and vascular reconstruction were also performed at the same time, if indicated, reflecting the complexity of the surgical management issues [47]. Five of the six patients were satisfied with the results [47].…”
Section: Surgerymentioning
confidence: 97%
See 1 more Smart Citation
“…& Localized microsurgical digital sympathectomy has been claimed to be a successful yet safer alternative to conventional surgical sympathectomy, with relatively few complications [64,65]. However, a systematic review of the outcomes of digital sympathectomy revealed that the perioperative complication rate among scleroderma patients was 37% [66].…”
Section: Localized Microsurgical Digital Sympathectomymentioning
confidence: 99%